SENTENCING OF CHILD OFFENDERS UNDER 14 YEARS OLD IN CASES OF SEXUAL VIOLENCE AGAINST CHILDREN BASED ON THE PRINCIPLE OF THE BEST INTERESTS OF THE VICTIM - Geraldo Gracelo Mario Situmeang; Setiawan Noerdajasakti; Abdul Madjid (CV. RADJA PUBLIKA, 2025)
The imposition of sanctions on child offenders under 14 years old in cases of sexual violence against children presents a legal dilemma between protecting the child offender and upholding the rights of the victim. Law No. 11 of 2012 on the Juvenile Justice System (Law on Juvenile Justice System) stipulates that children under 14 years old may only be subjected to measures, while Law No. 12 of 2022 on Sexual Violence Crimes (Law on Sexual Violence Crimes) emphasizes victim protection and recovery. This article examines the imbalance between these two regulations and analyzes the most appropriate sanctions based on the principle of the best interests of the victim. Using a normative juridical approach and case studies, it is found that while the Law on Juvenile Justice System aims to protect child offenders from the adverse effects of criminal sanctions, in cases of sexual violence against children, this approach risks neglecting victims’ rights. Therefore, a more flexible legal interpretation is needed to ensure that sanctions not only focus on the offender but also consider justice for the victim.